Literary visions of multicultural Ireland : The immigrant in contemporary Irish literature - Villar-Argaiz, Pilar (Book collections on Project MUSE., 2014)
Literary visions of multicultural Ireland is the first full-length monograph in the market to address the impact that Celtic-Tiger immigration has exerted on the poetry, drama and fiction of contemporary Irish writers. The book opens with a lively, challenging preface by Prof. Declan Kiberd and is followed by eighteen essays by leading and prestigious scholars in the field of Irish studies from both sides of the Atlantic who address, in pioneering, differing and enriching ways, the emerging multiethnic character of Irish literature. Key areas of discussion are: What does it mean to be 'multicultural,' and what are the implications of this condition for contemporary Irish writers? How has literature in Ireland responded to inward migration? Have Irish writers reflected in their work (either explicitly or implicitly) the existence of migrant communities in Ireland? If so, are elements of Irish traditional culture and community maintained or transformed? What is the social and political efficacy of these intercultural artistic visions? While these issues have received sustained academic attention in literary contexts with longer traditions of migration, they have yet to be extensively addressed in Ireland today. The collection will thus be of interest to students and academics of contemporary literature as well as the general reader willing to learn more about Ireland and Irish culture. Overall, this book will become most useful to scholars working in Irish studies, contemporary Irish literature, multiculturalism, migration, globalisation and transculturality. Writers discussed include Hugo Hamilton, Roddy Doyle, Colum McCann, Éilís Ní Dhuibhne, Dermot Bolger, Chris Binchy, Michael O'Loughlin, Emer Martin and Kate O'Riordan, amongst others.